Occupational Health Effects and Factors Associated with Safety Knowledge, Attitudes, and Practices among Latex Farmers in Southern Thailand - Pimpenjun Pan-in; Pimpiengjun Pan-in; Buacharoen, Thanawan; Decharat, Somsiri (National Journal of Community Medicine, 2026)
Background: Latex farmers engaged in fresh latex trading face multiple occupational hazards, including chemical exposure, job stress, musculoskeletal disorders, skin diseases, and respiratory symptoms. These hazards indicate the need for effective occupational safety and health management. This study aimed to assess occupational health effects and identify factors associated with safety knowledge, attitudes, and practices among latex farmers in southern Thailand. Methods: A cross-sectional study was conducted among 496 latex farmers selected by multistage sampling from agricultural cooperatives in three districts of southern Thailand. Data were collected using structured questionnaires covering demographics, work characteristics, health symptoms, and occupational safety knowledge, attitudes, and practices. Descriptive statistics, correlation analysis, and multiple regression analysis were applied with statistical significance defined at 0.05. Results: Most participants were male, middle-aged, and married, with education beyond secondary level. Many reported smoking, alcohol consumption, long working hours, no underlying diseases, and no prior safety training. Common health symptoms included musculoskeletal pain, eye irritation, and skin problems. Safety knowledge and safety attitudes were significantly associated with safety practices, explaining 35.1% of the variance in regression analysis. Conclusions: Enhancing safety knowledge and attitudes may be important correlates of safe work practices among latex farmers.